Extraction of gold from tailings using environmentally friendly reagents - Khuduwe, Marema Jack (University of the Witwatersrand, Johannesburg, 2024)
The depletion of high-grade gold ores, the high production costs associated with mining at lower depths, and the high demand for gold have caused the mining industry to search for alternative sources of gold. Additionally, the conventional cyanidation process raises health and environmental concerns. The treatment of waste generated by the cyanidation process to reduce the residual cyanide content before disposal also incurs additional costs. Therefore, this study focuses on the extraction of gold from tailings using environmentally benign reagents such as 1-butyl-3-methyl-imidazolium hydrogen sulfate (BmimHSO4) ionic liquid (IL), ethaline (mixture of choline chloride and ethylene glycol) deep eutectic solvent (DES), and thiosulfate. The gold tailings used in this work were obtained from DRD Gold Ergo Mining (Pty) Ltd operations in the Witwatersrand Basin, South Africa. Mineralogical analysis by X-ray diffraction (XRD) showed that the tailings material consisted of quartz (72.13%), muscovite (7.49%), chlorite (2.65%), pyrophyllite (1.50%), clinochlore (1.30%), and other trace minerals. The gold association by mineral liberation analysis (MLA) employing the Sparse Phase Liberation-Dual Zoom (SPL-DZ) method indicated that all the gold was locked in the iron oxide (FeO) matrix. Gold grade analysis by fire assay analysis (FAA) showed that the tailings had a head grade of 0.32 g/t Au. The leaching of the gold tailings was carried out by employing the use of the design of experiments (DOE) method to identify factors that significantly influence the gold extraction process. The central composite design (CCD) technique in conjunction with response surface methodology (RSM) was used to optimize the identified significant factors to obtain optimum conditions for optimal gold extraction. The effect of particle size and the co-dissolution of Ag, Cu, Fe, and Ni with Au was investigated. Furthermore, the recovery of Au by activated carbon (AC) from leach solutions of the investigated reagents was also investigated The results from the IL studies indicated that the reagent concentration had a positive and significant influence on the gold extraction process, suggesting that to achieve optimal gold extraction, IL concentration must be kept at a high level. The interaction of temperature, concentration, and pulp density also significantly influenced the gold extraction process in the IL solution. The theoretical optimum conditions established from the statistically-based optimization model were 75 C leaching temperature, 1.0 M (25% aqueous BmimHSO4 Extraction of gold from tailings using environmentally friendly reagents Marema J Khuduwe 4 mixture ) IL concentration, and 10 %w/v pulp density, giving a maximum Au extraction of 45.3%. This low Au extraction is attributed to the inefficiency of ILs in dissolving metals from their solid oxide form, thus unable to liberate the gold for dissolution locked in the metal iron oxide. On the other hand, leaching studies focusing on the use of DES found that pulp density and leaching time had a significant and positive influence on the gold extraction process. This suggests that to achieve maximum gold extraction, pulp density and leaching time must be kept at high levels. The optimum conditions were found to be 30 %w/v pulp density and 7 hrs leaching time. A maximum Au extraction of 76.4% was achieved. This high gold extraction is attributed to the high FeO destruction observed in the study, suggesting that the gold was liberated and amenable to leaching. Lastly, thiosulfate leaching studies identified temperature, time, pulp density, the interaction of temperature and concentration, the interaction of concentration and pulp density, and the interaction of temperature and time as the parameters significantly influencing gold extraction. A maximum Au extraction of 47% was achieved. This low gold extraction is attributed to the low efficiency of thiosulfate in dissolving metal iron oxide and the reagent consumption through silica dissolution, thus reducing the amount of thiosulfate available for gold dissolution. The results of the effect of tailings particle size results revealed that the IL leaching of bulk tailings (-300 m, P80 = 75 m) gave Au extraction of 21.9% while the leaching of smaller particle size tailings (-38 m) increased Au extraction to 45.3%. The high gold extraction at smaller particle sizes is attributed to the large surface area available for interaction with the leaching agent and the presence of a thin boundary, thus resulting in improved leaching efficiency. On the other hand, DES leaching of bulk tailings resulted in Au extraction of 71.9% and the leaching of smaller particle size tailings gave 76.4% Au extraction, indicating that reduction in particle size did not have a significant impact on gold dissolution. Lastly, thiosulfate leaching of bulk tailings gave a maximum Au extraction of 24% and the leaching of smaller particle size tailings resulted in an increased Au extraction of 47%, indicating that a reduction in particle size in this system had a significant effect. The study indicated that DES was more efficient in the dissolution of gold tailings compared to the use of IL and thiosulfate. Furthermore, DES gave higher Au extraction (71.6%) compared to cyanide solutions which gave Au extraction of 46.9%. However, cyanide gave a higher Au extraction compared to IL (21.9%) and thiosulfate (24%). These results indicate that ethaline DES is more efficient compared to 1-butyl-3-methyl-imidazolium hydrogen sulfate IL Extraction of gold from tailings using environmentally friendly reagents Marema J Khuduwe 5 and thiosulfate, and thus can be used in the processing of this kind of tailings as an alternative to cyanide. Moreover, the reagents dissolved more gold compared to other metals in the tailings except for IL which dissolved more Cu (50.4%) and Ni (61.9%) compared to Au (45.3%). Finally, the recovery of gold from the leach solution of the investigated reagents using activated carbon (AC) was found to be possible with the maximum Au adsorption of 84.6% achievable from IL leach solution in 2 hours at AC amount of 60 g/l and 4 hours at AC amount of 120 g/l. The maximum Au adsorption of 75% was achieved from DES leach solution in 4 hours at an AC amount of 120 g/l. The highest Au adsorption of 46.4% was achieved from thiosulfate leach solution in 6 hours. The recovery of Au by AC from leach solutions of IL and DES was high, however, they are not comparable to the 99% gold recovery by AC from cyanide solutions in the industry. This indicates that the recovery of gold from these solutions by alternative adsorbents should form a basis for further investigation.
A research report submitted in fulfillment of the requirements for the Master of Science in Engineering, In the Faculty of Engineering and the Built Environment , School of Chemical and Metallurical Engineering, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; gold mine tailings; leaching; ionic liquid; deep eutectic solvent; thiosulphate; cyanidation; SDG-12: Responsible consumption and production